Organisational flexibility in an age of chaos : mismanagement, disorganisation and strategy - Hatum, Andre??s (Routledge, 2026)
This groundbreaking book challenges conventional management wisdom by arguing that mismanagement and disorganisation are not failures but endemic features of organisational life in turbulent times. Through rigorous theoretical analysis and rich case studies, including an in-depth examination of Netflix, the author develops a comprehensive framework of organisational flexibility based on five key dimensions that enable companies to thrive amid chaos and uncertainty. The book offers several distinctive features: A provocative reconceptualisation of organisational adaptation; an empirically grounded framework for building flexible organisations; practical diagnostic tools for assessing and enhancing organisational adaptability; and detailed case studies that illuminate how successful organisations navigate complexity. Each chapter combines theoretical depth with practical insights, making complex concepts accessible while maintaining scholarly rigor. Written primarily for academics and researchers in organisation studies, strategic management, and leadership theory, this book will particularly appeal to doctoral students and advanced postgraduate scholars. It serves as an essential resource for management faculty teaching graduate courses in organisational behaviour, strategic change, and leadership, while also offering valuable insights for researchers studying organisational adaptation in volatile environments.
Keywords: Organizational change.; Organizational resilience.; elektronické knihy; electronic books